2008
DOI: 10.1128/aem.01261-08
|View full text |Cite
|
Sign up to set email alerts
|

Metalloprotease Vsm Is the Major Determinant of Toxicity for Extracellular Products ofVibrio splendidus

Abstract: Genomic data combined with reverse genetic approaches have contributed to the characterization of major virulence factors of Vibrio species; however, these studies have targeted primarily human pathogens. Here, we investigate virulence factors in the oyster pathogen Vibrio splendidus LGP32 and show that toxicity is correlated to the presence of a metalloprotease and its corresponding vsm gene. Comparative genomics showed that an avirulent strain closely related to LGP32 lacked the metalloprotease. The toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 34 publications
2
77
0
Order By: Relevance
“…Moreover, it has been found that this strain possesses the pathogenic factor vsm, a metalloprotease recently demonstrated to be the most important toxicity factor in the extracellular products of LGP32 (Binesse et al 2008). It is likely that this pathogenic factor is associated with the significant degranulation of Mya arenaria haemocytes in the present study.…”
Section: Discussionsupporting
confidence: 47%
“…Moreover, it has been found that this strain possesses the pathogenic factor vsm, a metalloprotease recently demonstrated to be the most important toxicity factor in the extracellular products of LGP32 (Binesse et al 2008). It is likely that this pathogenic factor is associated with the significant degranulation of Mya arenaria haemocytes in the present study.…”
Section: Discussionsupporting
confidence: 47%
“…Metalloproteases have several catalytic activities related to virulence but little is known about the diversity of these potential virulence factors in coral pathogenic bacteria. In the bivalve pathogen V. splendidus, the deletion of the Vsm metalloprotease resulted in the expression of other metalloproteases that were found to compensate for some of the functions fulfilled by the vsm gene product (Binesse et al, 2008). In the fish pathogen V. anguillarum, mutants lacking a functional EmpA metalloprotease expressed two different proteases that were not detected in the wild-type strain suggesting that these proteases might compensate for the loss of EmpA (Milton et al, 1992;Varina et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Alleles carrying an internal deletion were generated in vitro using a two-step PCR construction method (Binesse et al, 2008). Using genomic DNA of the strain P1, two independent PCR amplifications of 500 bp regions encompassing vcpA (GeneBank accession number GQ452012) were performed using primer pairs: C1: 5 0 -gcccgaattcATGAAACAACGTCAAATG CTTTGGC-3 0 and C2: 5 0 -CAAAACCTTTACGTACAT CCCAACGCAACAAAAAAGTCTACCATGTAAACG-3 0 ; or C3: 5 0 -CGTTTACATGGTAGACTTTTTTGTTGCG TTGGGATGTACGTAAAGGTTTTG-3 0 and C4: 5 0 -gcc cgaattcTTAGTCTAATCTTAGTGTCACGC-3 0 (Lower nucleotides are EcoRI enzyme sites).…”
Section: Bacterial Strains Plasmids and Mediamentioning
confidence: 99%
“…This Vibrio has been associated with major oyster summer mortality outbreaks over the past 15 years (Gay et al 2004a), and the strain V. splendidus LGP32 causes mortalities when injected to oysters (Gay et al 2004b;Le Roux et al 2007). The genome of V. splendidus was sequenced (Le Roux et al 2009), and several potential virulence factors were identified (Binesse et al 2008;Duperthuy et al 2010). The genome is nearly 5 Mb, 20% larger than that of V. cholerae, and V. splendidus chromosome II is 56% larger than its V. cholerae counterpart, indicating the possibility of many new sRNAs being present in this species.…”
Section: Introductionmentioning
confidence: 99%